PENERAPAN TEKNOLOGI TRANSPLANTASI DAN RESTORASI KARANG UNTUK MENINGKATKAN PENDAPATAN MASYARAKAT NELAYAN DI PERAIRAN DESA TANJUNG TIRAM, KABUPATEN KONAWE SELATAN, SULAWESI TENGGARA - Riska, Riska; Lalang, Lalang; Ode, Altafakur La; Ardiansyah, Indra; Kaatu, Kasnia (Universitas Mataram, 2024)
Coral reef ecosystems are highly vulnerable to damage. Various environmentally harmful activities by the community in the waters of Tanjung Tiram Village have led to the degradation of coral reefs. One of the efforts made to preserve and maintain coral reef ecosystems is the application of coral transplantation and restoration technology. This community service (PkM) activity aims to rehabilitate the coral reef ecosystem in collaboration with the partner group, Kelompok Harapan Bersama. The methods used to support the implementation of the PkM program include socialization, training, and demonstrations on coral rehabilitation techniques using the spider web-shaped hexagonal frame method. This method involves planting coral fragments or pieces into damaged areas, with the hope that the coral will grow and thrive, thereby restoring the ecological function of the coral reef ecosystem. The application of coral transplantation and restoration technology involves several stages, from preparation, transplantation, and restoration implementation, to maintenance for the sustainability of the coral reef ecosystem. The use of coral transplantation and restoration technology has become a promising solution for coral reef ecosystem restoration efforts. This technology has been proven effective in various areas and provides positive results, both ecologically and economically. The PkM activity received a positive and enthusiastic response from the partner group, with the coral transplantation area potentially becoming a new fishing ground for the local fishing community. An aquatic environment with a healthy coral reef ecosystem will produce abundant fish resources.